Direct PCR Based Detection of Macrophomina Phaseolina From Soil of Jute Field - Biswas, Chinmay; Dey , Piyali; Babu, Veegala Ramesh (Bangladesh Journal of Botany, 2024)
Macrophomina phaseolina (Tassi) Goid. is a devastating fungal pathogen which infects a large number of economically important crops. In jute, it mainly causes seedling blight, leaf spot, and stem rot. The pathogen is seed borne as well as soil borne. Macrophomina phaseolina pathogen was detected in soil samples collected from jute field by a direct PCR method (dPCR) without DNA isolation using ITS2 and ITS3 region specific primers designed during the present study. The soil samples were prepared in a lysis buffer and were incubated at 650C for 15 min. The optimized buffer system was composed of 200 mM tris (hydroxymethyl aminomethane (Tris)-Cl (pH 8.0), 3.5 mM ethylene diamine tetra acetic (EDTA) (pH 8.0), 4 M NaCl and 200 μg/ml Proteinase K. Further, β-marcaptoethanol (1% v/v) was added into the buffer. Bangladesh J. Bot. 53(2): 401-404, 2024 (June)